Weed flora in rice field of Tanjung Karang costal area in Malaysia. - Hakim, M. A.; Juraimi, Abdul Shukor; Musa, Mohamed Hanafi; Selamat, Ahmad; Ismail, Mohd Razi; Anwar, Md. Parvez (WFL Publisher, 2011)
The weed flora associated with rice crop in the coastal region of Peninsular Malaysia was studied. Through this research the competitive and harmful weeds of rice were identified, which could be helpful in planning their effective control and management. The research aimed to develop appropriate weed management technology on selected salt tolerant rice varieties as well as to develop package of production technologies for rice in coastal region of Tanjong Karang. A survey was conducted at 32 different rice fields in coastal area of Tanjong Karang in West Malaysia to identify most common and prevalent weeds associated with rice. Field survey was done according to the quantitative survey method by using 0.5 m x 0.5 m size quadrate with 20 samples from each field. A total of 39 different weed species belonging to 15 families were identified of which 23 were annual and 16 perennial; 10 grassy weeds, 9 sedges and 20 broadleaved weeds. Fimbristylis miliacea, Echinochloa crusgalli, Leptochloa chinensis, E. colona, Jussia linifolia, Cyperus iria, Sphenoclea zeylanica, Limnocharis flava, Cyperus deformis and Oryza sativa L. (weedy rice) were most frequent species covering more than 50% of fields. Based on relative abundance indices, annuals were more dominant than perennials, Fimbristylis miliacea, Echinochloa crusgalli, Leptochloa chinensis and E. colona were most prevalent and abundant species out of the 10 most dominant weed species in the coastal rice field of Tanjong Karang in Peninsular Malaysia.